A mesoscale finite element modeling approach for understanding brain morphology and material heterogeneity effects in chronic traumatic encephalopathy. Issue 11 (8th September 2021) - Bakhtiarydavijani, A.; Khalid, G.; Murphy, M. A.; Johnson, K. L.; Peterson, L. E.; Jones, M.; Horstemeyer, M. F.; Dobbins, A. C.; Prabhu, R. K.
Abstract: Chronic Traumatic Encephalopathy (CTE) affects a significant portion of athletes in contact sports but is difficult to quantify using clinical examinations and modeling approaches. We use an in silico approach to quantify CTE biomechanics using mesoscale Finite Element (FE) analysis that bridges with macroscale whole head FE analysis. The sulci geometry produces complex stress waves that interact with one another to create increased shear stresses at the sulci depth that are significantly larger than in analyses without sulci (from 0.5 to 18.0 kPa). Sulci peak stress concentration regions coincide with experimentally observed CTE sites documented in the literature. Highlights: Sulci introduce stress localizations at their depth in the gray matter Sulci stress fields interact to produce stress concentration sites in white matter Differentiating brain tissue properties did not significantly affect peak stresses